Hostile Attribution Bias and Anger Rumination Sequentially Mediate the Association Between Trait Anger and Reactive Aggression - Quan, Fangying; Wang, Lu; Gong, Xinyu; Lei, Xiaofang; Liang, Binqi; Zhang, Shuyue (Frontiers in Psychology, 2022)
Reactive aggression is a type of aggression that has severe consequences in individual’s psychosocial development and social stability. Trait anger is a risk personality factor for reactive aggression. However, the mediating mechanism of this relationship has not been sufficiently analyzed. We proposed that hostile attribution bias and anger rumination may be cognitive factors that play mediating roles in the relationship between trait anger and reactive aggression. To test this hypothesis, a sample of 600 undergraduates (51.67% females, Mage = 20.51, SD = 1.11) participated in this study. Findings showed that hostile attribution bias, anger rumination sequentially mediated the association between trait anger and reactive aggression. These results highlight the importance of anger rumination and hostile attribution bias to explain the link between trait anger and reactive aggression in undergraduates. The findings of the present study also provide valuable information about the role of negative cognitive activities (e.g., hostile attribution, ruminate in anger emotion) in high trait anger individual may trigger reactive aggression. The limitations of the study are discussed, along with suggestions for future research.